Ekklesiologiese perspektiewe op die geskiedenis van die NGKA-Ring van Lesotho tot 1998 - Beukes, Gideon Josua (University of the Free State, 2001)
Perspectives on the history of the Presbytery of the Dutch Reformed Church in Africa in Lesotho does not only portray its story, but also places it in a broad church historical frame of reference. The first chapter is therefore a synoptic exposition of the relationship between the Paris Evangelical Missionary Society (PEMS) and the Dutch Reformed Church of the Orange Free State (DRC OFS). In 1910 the Dutch Reformed Mission Church (DRMC) of the OFS was instituted, which means that the PEMS had to relate to the two neighbour churches. In this regard the DRC OFS shifted to the background. Between 1947 and 1957 the three churches (the PEMS by now became the Kereke ea Lesotho) were through their respective synodical commissions involved in bilateral discussions concerning the ministry to LEC members in the Goldfields of the Free State. In the end it was decided that the LEC should take on the responsibility herself. At the very same time the DRMC OFS and the DRC OFS were collaborating in planning and implementing a joint mission enterprise in Basotholand. During 1957 the first missionaries were called and ordained, in 1960 the first DRMC congregation were instituted and in October 1963 the Presbytery of Basotholand constituted for the first time. Thus a DRCA church was planted in Lesothothe traditional area where the Kereke ea Lesotho worked for more than 130 years. The presbytery was lead by ecclesiastical structures (liaison committees) that took the initiative and made the decisions. Early in the seventh decade expansion into the mountains was made possible by the involvement of the DRC congregation of Bothaville. The emphasis was now on evangelizing and a building programme. However, in the eighties, the enterprise faced a crisis. There were shortages on the budget and the one disciplinary hearing after the other that hampered the spirirtual development of the Presbytery. During these crisis years the ministers and evangelists realised that a thorough theological and ecclesiastical assessment should be made. During 1987 this started and eventualy (after 1995) resulted in recocnizing that the Presbytery has come to age to take on ministerial responsabilities as the true expression and embodyment of the mutual connectedness betweenthe (now) eight Lesotho congregations.

In Ekklesiologiese Perspektiewe op die geskiedenis van die NGKARing van Lesotho word nie net die verhaal van hierdie Ring weergegee nie, maar ook in kerkhistoriese perspektief vereken. Dit is dus in 'n breëre verbandlegging geplaas en beskryf. Daarom is die hele eertse hoofstuk daaraan afgestaan om 'n oorsig te gee van die verhouding van eers die PESG met die NGK OVS tot min of meer 1900. Gedurende die twintigste eeu het die PESG al meer die Kereke ea Lesotho geword en met die NGSK OVS ná 1910 bande geknoop, terwyl die NGK OVS op die agtergrond geraak het. Tussen 1947 en 1957 het die kerklike kommissies van die drie kerke dikwels vergader. Hulle was op soek na 'n bevredigende verstandhouding met betrekking tot die bediening van lidmate van die Kereke ea Lesotho wat na die Vrystaatse Goudvelde gekom het ter wille van 'n heenkome. Uiteindelik het hulle aanvaar dat kerke ook in die Vrystaat en Lesotho onderskeidelik sal werk. Dit gebeur terwyl die NGSK OVS en NGK OVS 'n gesamentlike sendingaksie in Basotholand beplan en na 1957 ook loods met die beroeping van werkkragte. Net na 1960 is die eerste gemeentes gestig en in 1963 word die Ring van Basotholand geïntitueer. Hierdie Ring is aan die hand geneem deur die kerklike skakelliggame wat deur die NGK/NGSK daar gestel is. Hierdie ljggame het in werklikheid die rol van 'n kerkverband gespeel. In die sewentiger jare is die sendingaksie met die steun van die NG gemeente Bothaville tot diep in die berge uitgebrei, met die klem nou op evangelisering. Ondertussen het die begroting dramaties gestyg. Die instandhouding van die bouprogram wat in 1966 geloods is het duur gekos. Die een tugsaak na die ander het afbrekend die sending onderneming gestrem. 'n Krisis het ontwikkel. In 1987 sou 'n indringende debat en teologiese verantwoording eers die leraars en evangeliste in Lesotho en later die Ring betrek. Dit is hierdie verantwoording wat meegebring het dat die Ring van Lesotho homself erken het as die verband tussen die (nou) agt gemeentes in Lesotho.
Dissertation (M.Th. (Ecclesiology))--University of the Free State, 2001
Keywords: Churches in Lesotho; Churches in the Orange Free State; History of the Dutch Reformed Mission Church in the Free State; Paris Evangelical Mission Society; Lesotho Evangelical Church; Presbytery of the Dutch Reformed Church in Africa in Lesotho; Church history Lesotho; Relationship Lesotho Evangelical Church and the Dutch Reformed Church; Church history -- Lesotho; Christian union